Analysis of Pronunciation Difficulties In Arabic - Afifah, Evi; Mahmud, Basri; Hamzah, Hamzah; Afiah, Nur; Mujahid, Mujahid (Al-Wazan: Journal of Arabic Education, 2024)
The integrated system used in language learning in class V of MI Ddi Kanang makes the hour for learning Arabic in four hours with two meetings for one week. This makes learning opportunities with Arabic speaking less considering that the lesson requires a lot of practice. This study aims to analyze the difficulties of pronunciation in Arabic in class V MI DDI Kanang. This type of research is qualitative research with a descriptive design. This study describes the Analysis of Arabic Pronunciation Errors in Class V of V MI DDI Kanang. The data in this study consists of primary data in the form of data collected directly by researchers from the first source (respondents) in the field. The main source in this study is the class V education student of MI DDI Kanang. Meanwhile, secondary data is data obtained indirectly through intermediary media. The results of the observation from the analysis of pronunciation difficulties in Arabic in class V MI DDI Kanang Polewali Mandar include the factors that cause difficulties in pronunciation of Arabic for students in class V MI DDI Kanang, The first, is the lack of proficiency of students in reciting the Qur'an, the second is the lack of interest and motivation from the students themselves to learn Arabic, the third is the lack of attention from parents to students regarding awareness and encouragement to learn outside of school, the Fourth is the teacher's delivery technique that is too monotonous, namely only using lecture techniques and package book facilities provided by the school are very limited so that Arabic learning is less effective and raises various obstacles.